Characterization of Flower-like Titanate and Titania Nanowires on Titanium Plate Substrate - Sorapong Pavasupree; Kinji Onoda; Susumu Yoshikawa; Athapon Simpraditpan; Wisanu Pecharapa (My University, 2013)
Flower-like structure titanate and titania on titanium plate substrate composed of nanowires were synthesized by hydrothermal method at 150 oC for 2 h using titanium plate substrate as the starting material. The crystalline structure, shape and size of the prepared sample were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM). SEM images showed flower-like structure with uniform size about 2 μm. The flower-like structure composed of nanowires with diameter about 20-50 nm. Titanate and titania could be controlled by washing process and calcination temperature. This synthesis method provides a simple route to fabricate nanostructured titanate and titania on titanium plate substrate for dye-sensitized solar cell and photocatalytic activity applications.
Keywords: TiO2 Photocatalysis and Solar Cells